Influence of Fuel Temperature on Diesel Engine Performance Operating With Biodiesel Blend - Rafidah, Rahim; R., Mamat; Mohd Yusof, Taib; Abdul Adam, Abdullah (Faculty Mechanical Engineering, UMP, 2012)
This paper presents the study of the effect of temperature on diesel engine performance using a 5% biodiesel blend. A one-dimensional numerical analysis is used to simulate the four-cylinder diesel engine. The diesel engine simulation is used to study the characteristics of engine performance when the engine is operating with a fuel blend as an alternative fuel. The simulations are conducted at full load conditions where the temperature varies from 300 to 500 K. The results show that the maximum brake power and brake torque reduction was 1.39% and 1.13%, respectively for an engine operating with a fuel blend. It is shown that the insignificant different due to the small gap between energy content values. A decrease in the lower heating value caused an increase in the brake specific fuel consumption and thus, a reduction in the brake thermal efficiency of the engine performance at full load.